Games : the multi award-winning multiformat games magazine. (Bournemouth : Imagine)
Highly respected within the industry by both publishers and development studios alike, games has proved itself as one of the most esteemed and trusted magazines in the field. The soaring production values and highly knowledgeable team have already secured four industry awards, and the unflinching and unbiased opinion has elevated the magazine's status to one of the most trusted in the business. At a massive 180 pages and with dedicated sections for retro gaming, market news, and recruitment, games is the easily the most comprehensive videogame magazine on the market and the perfect choice for anyone who takes gaming seriously